Deficits in physiological and self-conscious emotional response to errors in hoarding disorder. (October 2018) - Zakrzewski, Jessica J.; Datta, Samir; Scherling, Carole; Nizar, Krystal; Vigil, Ofilio; Rosen, Howard; Mathews, Carol A.
Highlights: Individuals with HD had hypo active responses to errors. Individuals with HD self-reports were opposite of their facial responses to errors. Individuals with HD exhibit dissociation between perception and emotional reactions. Abstract: Hoarding disorder (HD) has been hypothesized to arise from deficits in error monitoring and abnormalities in emotional processing, but the relationship between error monitoring and emotional processing has not been examined. We examined measures of self-report, as well as behavioral, physiological, and facial responses to errors during a Stop-Change Task. 25 participants with HD and 32 healthy controls (HC) were recruited. Participants reported on number of errors committed and pre/post emotional response to errors. Skin conductance response (SCR) during correct and error commission trials was examined. Facial expression during task performance was coded for self-conscious and negative emotions. HD and HC participants had significantly different error rates but comparable error correction and post-error slowing. SCR was significantly lower for HD during error commission than for HC. During error trials, HD participants showed a significant deficit in displays of self-conscious emotions compared to HC. Self-reported emotions were increased in HD, with more negative and self-conscious emotion reported than was reported for HC participants. These findings suggest that hypoactive emotional responding at a physiological level may play a role in how errors are processed in individuals with HD.